AP2/ERF Family Transcription Factors ORA59 and RAP2.3 Interact in the Nucleus and Function Together in Ethylene Responses - Kim, Na Young; Jang, Young Jin; Park, Ohkmae K. (Frontiers in Plant Science, 2018)
The gaseous plant hormone ethylene is a key signaling molecule regulating plant growth, development, and defense against pathogens. OCTADECANOID-RESPONSIVE ARABIDOPSIS 59 (ORA59) is an ETHYLENE RESPONSE FACTOR (ERF) transcription factor and has been suggested to integrate ethylene and jasmonic acid signaling and regulate resistance to necrotrophic pathogens. Here we screened for ORA59 interactors using the yeast two-hybrid system to elucidate the molecular function of ORA59. This led to the identification of RELATED TO AP2.3 (RAP2.3), another ERF transcription factor belonging to the group VII ERF family. In binding assays, ORA59 and RAP2.3 interacted in the nucleus and showed ethylene-dependent nuclear localization. ORA59 played a positive role in ethylene-regulated responses, including the triple response, featured by short, thick hypocotyl and root, and exaggerated apical hook in dark-grown seedlings, and resistance to the necrotrophic pathogen Pectobacterium carotovorum, as shown by the increased and decreased ethylene sensitivity and disease resistance in ORA59-overexpressing (ORA59OE) and null mutant (ora59) plants, respectively. In genetic crosses, ORA59OE rap2.3 crossed lines lost ORA59-mediated positive effects and behaved like rap2.3 mutant. These results suggest that ORA59 physically interacts with RAP2.3 and that this interaction is important for the regulatory roles of ORA59 in ethylene responses.